Optimalisasi Penambahan Rumput Laut (Eucheuma cottoni) dengan Konsentrasi 2%, 4%, 6% dan 8% Terhadap Sifat Fisik Sosis Ikan Lele (Clarias gariepinus) - Tyas Wara Sulistyaningrum (Fakultas Peternakan Universitas Kristen Palangka Raya, 2018)
This research aims to increase the usability of seaweed (Eucheuma cottoni) as one of the result of the waters of the sea, also to find out the optimum concetration of additional seaweed towards physical characteristic of catfish (Clarias gariepinus) sausage with the research benefit to utilize the seaweed optimally. The data were collected based on the result of monitoring towards physical experiment (folding test). Based on the result of the folding test toward catfish sausage so it could be conclude that the addition of 2% seaweed was the optimum adding, it stated in the value of the highest average score that was obtained in folding test (4.43). Keywords : optimalization, physical experiment, seaweed, sausage